Recruitment policy for educators and its implications on learning quality - Riva Zahra Rizkyani; Radita Dian Eka; Gina Fadillah; Ardhan Mardiant (Universitas Pendidikan Indonesia, 2025)
This article discusses the educator recruitment policy at the West Java Provincial Education Office and its implications for the quality of learning at SMA 19 Bandung. The policy of transferring recruitment authority from schools to the Education Office aims to equalize the distribution of educators, however, it poses challenges in aligning the specific needs of schools with the assigned teaching staff. This study aims to identify the impact of the recruitment policy on the learning process, explore the challenges faced by schools in implementing the policy, and formulate strategic solutions to improve the effectiveness of the recruitment system. This research uses a qualitative approach with a case study design through interviews, observations, and documentation studies. The results showed that the policy had an impact on the mismatch of educators with the needs of schools and the limited flexibility of schools in determining suitable educators. Continuous collaboration between schools and the education office needs to address these challenges through effective communication, educator evaluation and needs-based training. This research recommends a more flexible approach to educator recruitment and competency development policies to support improving education quality. Abstrak Artikel ini membahas kebijakan perekrutan tenaga pendidik di Dinas Pendidikan Provinsi Jawa Barat dan implikasinya terhadap kualitas pembelajaran di SMA 19 Bandung. Kebijakan yang mengalihkan kewenangan perekrutan dari sekolah ke Dinas Pendidikan bertujuan untuk meratakan distribusi tenaga pendidik, namun menimbulkan tantangan dalam menyelaraskan kebutuhan spesifik sekolah dengan tenaga pendidik yang ditugaskan. Penelitian ini bertujuan untuk mengidentifikasi dampak kebijakan perekrutan terhadap proses pembelajaran, mengeksplorasi tantangan yang dihadapi sekolah dalam implementasi kebijakan, dan merumuskan solusi strategis untuk meningkatkan efektivitas sistem perekrutan. Penelitian Ini menggunakan pendekatan kualitatif dengan desain studi kasus melalui wawancara, observasi, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa kebijakan tersebut berdampak pada ketidaksesuaian tenaga pendidik dengan kebutuhan sekolah dan terbatasnya fleksibilitas sekolah dalam menentukan tenaga pendidik yang sesuai. Tantangan ini perlu diatasi dengan kolaborasi berkelanjutan antara sekolah dan Dinas Pendidikan melalui komunikasi yang efektif, evaluasi tenaga pendidik, serta pelatihan berbasis kebutuhan. Penelitian ini merekomendasikan pendekatan yang lebih fleksibel dalam kebijakan perekrutan dan pengembangan kompetensi tenaga pendidik untuk mendukung peningkatan kualitas pendidikan secara keseluruhan. Kata Kunci: kebijakan perekrutan; kualitas tenaga pendidik; manajemen pendidikan